Bank investment management : building and maintaining a sound investment policy and program - Stevenson, T. Herbert (Chicago, IL : Bankers Pub. Co., 1993)
The book will be an invaluable tool for the investment officer, investment committee members, controllers, ALCO members, internal auditors, external auditors and any student of the industry seeking a better understanding of the investment function within financial institutions.
1 vol. loose leaf
osc 10/07/2018
Loans
Keywords: Banks; Bank Management